INFORMATION NEEDS OF MALAYSIAN BUMIPUTERA WOULD-BE ENTREPRENEURS - Kassim, Norliya Ahmad (Malaysian Journal of Library and Information Science, 2010)
This paper reports on the findings of a part of a study that aims to investigate the information needs of Malaysian Bumiputera entrepreneurs. The study adopted a quantitative approach and questionnaires were distributed to a sample of 400 Bumiputera would-be entrepreneurs who had attended entrepreneurial development courses. It was found that the types of business information needed by the respondents were preparation of business plan, followed by planning of cash flow, examination of business opportunities, and profit planning. The results indicated that the types of business information considered very important were information related to planning of cash flow, followed by preparation of business plan, profit planning, communications with clients, business opportunities, courses on entrepreneurship, and creativeness and innovativeness in business. The study found that respondents obtained most of their business information by talking to other entrepreneurs, followed by sharing experience with other entrepreneurs, discussing with friends/relatives, reading newspaper and magazines, and asking clients. The results revealed that the sources from which respondents obtained their business information were courses, followed by business exhibitions, Internet/e-mail, business premises, government agencies, and technical training. The respondents considered clients and other entrepreneurs as very important sources of business information. The study had a profound impact on making recommendations to business supporting agencies concerning entrepreneurs’ and business sectors’ information needs in Malaysia.